Cardiac and placental imaging (CARP) in pregnancy to assess aetiology of preeclampsia. (May 2022) - Colford, Kathleen; Price, Anthony N.; Sigurdardottir, Julie; Fotaki, Anastasia; Steinweg, Johannes; Story, Lisa; Ho, Alison; Chappell, Lucy C.; Hajnal, Joseph V.; Rutherford, Mary; Pushparajah, Kuberan; Lamata, Pablo; et al.
Abstract: Introduction: The CARP study aims to investigate placental function, cardiac function and fetal growth comprehensively during pregnancy, a time of maximal cardiac stress, to work towards disentangling the complex cardiac and placental interactions presenting in the aetiology of pre-eclampsia as well as predicting maternal Cardiovascular Disease (CVD) risk in later life. Background: The involvement of the cardiovascular system in pre-eclampsia, one of the most serious complications of pregnancy, is evident. While the manifestations of pre-eclampsia during pregnancy (high blood pressure, multi-organ disease, and placental dysfunction) resolve after delivery, a lifelong elevated CVD risk remains. Method: An assessment including both cardiac and placental Magnetic Resonance Imaging (MRI) optimised for use in pregnancy and bespoke to the expected changes was developed. Simultaneous structural and functional MRI data from the placenta, the heart and the fetus were obtained in a total of 32 pregnant women (gestational ages from 18.1 to 37.5 weeks), including uncomplicated pregnancies and five cases with early onset pre-eclampsia. Results: The achieved comprehensive MR acquisition was able to demonstrate a phenotype associated with pre-eclampsia linking both placental and cardiac factors, reduced mean T2* (p < 0.005), increased heterogeneity (p < 0.005) and a trend towards an increase in cardiac work, larger average mass (109.4 vs 93.65 gr), wall thickness (7.0 vs 6.4 mm), blood pool volume (135.7 vs 127.48 mL) and mass to volume ratio (0.82 vs 0.75). The cardiac output in the controls was, controlling for gestational age, positively correlated with placental volume (p < 0.05). Discussion: The CARP study constitutes the first joint assessment of functional and structural properties of the cardiac system and the placenta during pregnancy. Early indications of cardiac remodelling in pre-eclampsia were demonstrated paving the way for larger studies. Highlights: A comprehensive assessment of both cardiac and placental function during pregnancy. Step towards understanding the intertwined cardiac and placental pathways in PE. Pregnancy as a unique window of observation into pathophysiology and future cardiovascular risk. Placental parameters deviate significantly between PE and uncomplicated pregnancies. Early indications for a remodelling of the heart during PE are demonstrated.